Callus induction, clonal propagation and in vitro germplasm conservation of ‘hualtaco’ Loxopterygium huasango Spruce ex Engl. (Anacardiaceae) - Delgado Paredes, Guillermo (2021)
Loxopterygium huasango Spruce ex Engl., of the Anacardiaceae family, classified critically endangered, is a forest tree with considerable value in the Seasonally Dry Tropical Forest (SDTF) in the northwest of Peru and south of Ecuador. The aim of the study was callus induction, propagation and germplasm conservation using in vitro tissue culture techniques. In vitro seed germination (90%) was obtained on Murashige and Skoog (MS) medium supplemented with 5.0 mg/L-1 GA3. The cotyledonal nodes of seedlings were used as explants to initiate the growth of the apical shoots, in culture medium with the IAA-GA3 interactions, without observing growth of the axillary buds. The highest rate of friable callus induction (100%) was recorded on MS medium containing 0.1 to 5.0 mg/L-1 2,4-D in cotyledons and hypocotyls explants after 30 to 45 days of culture. The profuse roots formation was the only morphogenic response (10.8 to 13.8%) on MS medium with 0.5 mg/L-1 IAA, 0.5 mg/L-1 IAA 2.0 mg/L-1 BAP, KIN or 2iP or 2.0 mg/L-1 BAP, KIN or 2iP. The germplasm conservation of apical buds and nodal segments was achieved with 2.0 mg/L-1 AgNO3. This method could be used to conserve elite genotypes, rapid production of roots and establishment of cellular suspension for secondary compounds production.